Medical ethics and Islam: principles and practice. Issue 1 (1st January 2001) - Gatrad, A R; Sheikh, A
Abstract : A minimum level of cultural awareness is a necessary prerequisite for the delivery of care that is culturally sensitive. In this paper we simplify and highlight certain key teachings in Islamic medical ethics and explore their applications. We hope that the insights gained will aid clinicians to better understand their Muslim patients and deliver care that pays due respect to their beliefs.